Kemampuan Mahasiswa Program Studi Pendidikan Matematika FKIP Universitas Mataram dalam Membuat RPP dengan Menerapkan Model Problem Based Learning - Yenny Indriani; Sripatmi Sripatmi; Arjudin Arjudin; Sri Subarinah (Griya Journal of Mathematics Education and Application, 2021)
This study aims to determine the level of ability and describe the constraints of mathematics education students in making a learning implementation design with a problem based learning model. This type of research is descriptive exploratory with quantitative and qualitative approaches. The research population was all students in the 7th semester of the mathematics education study program, which were divided into 3 classes, namely classes A, B, and C. Sample of this study were 7 students who PLP courses. The results showed that there were 9 aspects of the learning implementation design assessment that would be assessed on 7 students. The average percentage of the 9 aspects assessed by researchers was 72.67% and those assessed by teachers were 73.67%, both of which were in the good category.